2010
DOI: 10.1179/174329210x12650506623645
|View full text |Cite
|
Sign up to set email alerts
|

Indoleamine 2,3-dioxygenase and 3-hydroxykynurenine modifications are found in the neuropathology of Alzheimer's disease

Abstract: Tryptophan metabolism, through the kynurenine pathway (KP), produces neurotoxic intermediates that are implicated in the pathogenesis of Alzheimer disease (AD). In particular, oxidative stress via 3-hydroxykynurenine (3-HK) and its cleaved product 3-hydroxyanthranilic acid (3-HAA) significantly damages neuronal tissue and may potentially contribute to a cycle of neurodegeneration through consequent amyloid-β accumulation, glial activation, and upregulation of the KP. To determine the role of the KP in elicitin… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
90
0
4

Year Published

2013
2013
2024
2024

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 113 publications
(96 citation statements)
references
References 55 publications
2
90
0
4
Order By: Relevance
“…Immunoreactivity for both IDO and QUIN have been observed in microglia, astrocytes and neurons of hippocampal tissue from AD patients, with the highest signal being observed at the perimeter of senile plaques in the brain [72]. Both are also found in neurofibrillary tangles and QUIN is present in intracellular granular deposits in cortical neurons [70] [72].…”
Section: Alzheimer's Diseasementioning
confidence: 84%
See 1 more Smart Citation
“…Immunoreactivity for both IDO and QUIN have been observed in microglia, astrocytes and neurons of hippocampal tissue from AD patients, with the highest signal being observed at the perimeter of senile plaques in the brain [72]. Both are also found in neurofibrillary tangles and QUIN is present in intracellular granular deposits in cortical neurons [70] [72].…”
Section: Alzheimer's Diseasementioning
confidence: 84%
“…As in HD, perturbation of the KP is strongly implicated in AD, with an increased L-KYN/TRP ratio found in the blood and CSF of AD patients compared to healthy individuals [69]. This altered ratio coincides with increased levels of IDO in the brain [70] and 3-HK in blood serum [71]. Immunoreactivity for both IDO and QUIN have been observed in microglia, astrocytes and neurons of hippocampal tissue from AD patients, with the highest signal being observed at the perimeter of senile plaques in the brain [72].…”
Section: Alzheimer's Diseasementioning
confidence: 99%
“…As with L-PS, elevated levels of 3-HAA and related metabolites have been found in postmortem brains with verified Alzheimer disease. 30 These observations raise the possibility that the increased level of 3-HAA occurring in the brains of people with Alzheimer disease may in fact be a protective response (although others have suggested its role to be causative, rather than curative, because of a possible role of 3-HAA in mediating neurotoxic oxidative stress). 30 …”
Section: -Hydroxyanthranilic Acidmentioning
confidence: 96%
“…With regard to the levels of these metabolites in AD tissues, though early studies demonstrated non-significant alterations in 3-OH-L-KYN levels in AD brains, recent immunohistochemical studies proved that 3-OH-L-KYN may considerably accompany to the damage of neuronal tissues, with its levels found to be significantly elevated in hippocampal neurons in AD compared to controls [216,230,231]. With regard to the periphery, markedly increased levels of 3-OH-L-KYN [232] as well as elevated levels of circulating IgA directed against 3-OH-L-KYN [233] were found in serum samples of AD patients, though a study found only a trend for 3-OH-L-KYN to be increased in the plasma of AD patients [234].…”
Section: -Hydroxy-l-kynurenine and 3-hydroxyanthranilic Acidmentioning
confidence: 99%